Training needs in construction project management: A survey of 4 countries of the EU - Teixeira, José Manuel Cardoso; Minasowicz, Andrzej; Zavadskas, Edmundas Kazimieras; Ustinovichius, Leonas; Migilinskas, Darius; Armiñana, Eugenio Pellicer; Nowak, Pawel Olaf; Grabiec, Mieczysław (Journal of Civil Engineering and Management, 2006)
Knowledge on construction project management is a key issue in today's construction industry across Europe. This applies to the whole range of project participants from inception to conclusion of construction undertakings thereby involving professionals focusing in distinct perspectives yet working for a common goal. Several countries in Europe, with special relevance to the UK, have developed substantial knowledge in this topic through academic courses, professional training and experience of practitioners. Other countries have not achieved this stage but the need to prepare professionals to work in the open European market is impelling efforts for convergence in this matter. This article reports a survey on professional training needs in four European countries presently partnering in a Leonardo da Vinci project on management of construction infrastructure projects. The survey was carried by a questionnaire administered to a set of organisations of the construction cluster of the four countries involved. Results were used for defining 6 areas of interest for CPD courses which are presently being developed in the scope of the project.Mokymo kursų poreikiai valdant statybos projektus: keturių ES valstybių apžvalgaSantrauka. Statybos projektų valdymo principų mokymas šiuo metu yra vienas iš pagrindinių tikslų visos Europos statybos pramonėje. Tai susiję su visais projekto dalyviais nuo pradžios iki statybos pabaigos. Taip į šią veiklą įtraukiami įvairūs specialistai, kurie siekia bendrų tikslų, bet dirba skirtingose statybos srityse. Kelios Europos valstybės, ypač Didžioji Britanija, kursų metu esmingai mokė įvairaus lygio specialistus. Kitos šalys nepasiekė šios stadijos, bet poreikiai parengti profesionalus dirbti atviroje Europos rinkoje suaktyvino pastangas šį klausimą spręsti. Šiame straipsnyje pateikta profesionalaus mokymo kursų poreikių analizės ataskaita keturiose Europos šalyse, kurios dalyvauja Leonardo da Vinci projekte, skirtame statybos infrastruktūros projektui valdyti. Analizė atlikta apklausos būdu. Apklausos anketos buvo nusiųstos keturių šalių statybos organizacijoms. Apklausos rezultatai naudojami nustatant šešis kursų dalykus, vykdomus šiame projekte.Raktiniai žodžiai: statyba, projektų valdymas, žinios, mokymas.First Published Online: 14 Oct 2010